2021
DOI: 10.1537/ase.201217
|View full text |Cite
|
Sign up to set email alerts
|

Modern human DNA analyses with special reference to the inner dual-structure model of Yaponesian

Abstract: Previous studies suggested two major migration events during the Jomon and Yayoi periods that affected the genetic diversity of modern Japanese (Yaponesians). We explored the possibility of a three-wave migration model by examining three datasets of modern human DNA: (1) whole mitochondrial (mt) DNA genomes of 1642 Yaponesians; (2) mtDNA haplogroup frequencies of 59105 Yaponesians from 47 prefectures; and (3) genome-wide SNP data of two Yaponesians (Ainu, Okinawa) and whole-genome sequence data of Yamato indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…This hypothesis was originally proposed on the basis of morphological data but has been widely tested and evaluated across disciplines [see a recent review in (6)]. Genetic studies have identified population stratifications within present-day Japanese populations, supporting at least two waves of migrations to the Japanese archipelago (7)(8)(9)(10). Previous ancient DNA studies have also illustrated the genetic affinity of Jomon and Yayoi individuals to Japanese populations today (11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis was originally proposed on the basis of morphological data but has been widely tested and evaluated across disciplines [see a recent review in (6)]. Genetic studies have identified population stratifications within present-day Japanese populations, supporting at least two waves of migrations to the Japanese archipelago (7)(8)(9)(10). Previous ancient DNA studies have also illustrated the genetic affinity of Jomon and Yayoi individuals to Japanese populations today (11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…We used the DNA specimens to perform a whole-genome SNV analysis (Asian Screening Array assay; 6 Genesis Healthcare, Tokyo, Japan) specified to East Asian populations, with the iScan System (Illumina, San Diego, CA, USA). Briefly, this analysis can comprehensively analyze approximately 660,000 SNVs.…”
Section: Methodsmentioning
confidence: 99%
“…Building on this previous research, we focus on the Japanese population as a case study of OR gene family variation. The Japanese population is a hybrid between the Yayoi people, farmers who migrated from the East Eurasian Continent ~3000 years ago, and the Jomon people, indigenous huntergatherers who were likely to be the descendants of late-Paleolithic people in the Japanese archipelago (Hanihara, 1991;Adachi et al, 2021;Jinam et al, 2021;Koganebuchi and Oota, 2021;Osada and Kawai, 2021). Ancient DNA analyses inferred that the Jomon people diverged from the current East Asians earlier than 26000 years ago (McColl et al, 2018;Gakuhari et al, 2020).…”
Section: Introductionmentioning
confidence: 99%